The Role of Tourism in Poverty Reduction In the Community of Sumbawa District: a case study of the Mangrove Forest in Dusun Omo Penyaring Village - Lismula, Riska Julianti Ade; Husaini, Husaini (UPI YPTK Journal of Business and Economics, 2024)
This study discusses the role of mangrove ecotourism in poverty reduction in the Dusun Omo community, Penyaring Village, Sumbawa Regency. Mangrove ecotourism is one initiative that is considered to be able to provide a positive impact on the welfare of local communities, both through job creation and increased income. This study used a mixed method, with data collected through surveys of communities involved in mangrove tourism, as well as in-depth interviews with stakeholders, such as tourism managers and community leaders. The results of the study showed that the development of mangrove tourism made a significant contribution to reducing poverty levels in Omo Hamlet. As many as 70% of respondents experienced an increase in income, and 25% of previously unemployed people now have jobs in the tourism sector. However, there are several challenges in managing this ecotourism, including the low capacity of local tourism management and the potential for environmental damage to the community. Therefore, further efforts are needed from the government and other stakeholders to ensure the desire for mangrove tourism as a means of poverty alleviation and environmental conservation.